Advances in Insect Control and Resistance Management - Horowitz, A. Rami; Ishaaya, Isaac (Springer International Publishing : Imprint: Springer, 2016)
This book covers advanced concepts and creative ideas with regard to insect biorational control and insecticide resistance management. Some chapters present and summarize general strategies or tactics for managing insect pests such as the principles of IPM in various crop systems and biorational control of insect pests, advances in organic farming, alternative strategies for controlling orchard and field-crop pests. Other chapters cover alternative methods for controlling pests such as disruption of insect reproductive systems and utilization of semiochemicals and diatomaceous earth formulations, and developing bioacoustic methods for mating disruption. Another part is devoted to insecticide resistance: mechanisms and novel approaches for managing insect resistance in agriculture and in public health.